Teknik Dan Metode Penerjemahan Kata-Kata Bijak (Meigen No Kotoba) Dalam Komik Naruto Volume 41-60 Karya Masashi Kishimoto - Sarhita Cindra Pratama, Putu; Gorethy Nie Nie, Maria; Oeinada, I Gede (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
The title of this thesis is “Translation Technique and Method of Wisdom Words (Meigen no Kotoba) in Manga Naruto Volume 41-60 by Masashi Kishimoto”. This study aims to analyze the translation technique and method that is used to translating wisdom words in manga Naruto. The theories used for analyzing are translation technique by Molina and Albir (2002) and translation method by Newmark (1998). The results of this research shows that from 63 data, there are eight technique applied, namely 32 data of literal translation, 10 data of established equivalent, 6 data of discursive creation, 5 data of amplification, 3 data of borrowing, 3 data of substitution, 3 data of reduction, 1 data of generalization. The translation method is source language oriented method.